(untitled) (Journal of Philosophy Culture and Political Science, 2026)
The article investigates the intersection of state religious policy and the phenomenon of multiple religious identity in the Republic of Kazakhstan from a political science perspective. Kazakhstan presents a distinctive governance case: a constitutionally secular post-Soviet state that simultaneously mobilizes Islamic cultural heritage as a national identity resource while maintaining a restrictive regulatory environment for non-institutional religious practice. Drawing on a mixed-methods research design that integrates legislative corpus analysis (1991-2024), comparative governance indices, open-access nationwide survey data, and expert interviews, the study demonstrates that the prevailing managed-pluralism governance model generates a structural paradox: informal religious plurality proliferates as citizens navigate constrained institutional channels. The analysis reveals that those religious cleavages – between believers and non-believers, and between adherents of traditional and non-traditional religions – are perceived as among the sharpest social divisions in contemporary Kazakhstan, ranking above ethnic and linguistic divides. The article advances a conceptual typology of state approaches to religious identity governance, constructs a Regulatory Restriction Index to trace policy trajectory across three distinct phases, and formulates evidence-based policy recommendations oriented toward deliberative pluralism. The findings contribute to comparative political science literature on religion-state relations in post-Soviet Central Asia and to broader debates on the governance of religious diversity in transitional democracies. Keywords: multiple religious identity; state religious policy; Kazakhstan; political secularism; governance; Islam; identity politics.